MODEL CONDITIONAL PROCESS PADA PENGARUH POLYCHRONICITY TERHADAP TURNOVER INTENTION KARYAWAN INDUSTRI PERHOTELAN - Rian Andriani, - (2020)
The growth of hotels in Indonesia as one of the hospitality industry is so rapid, but not balanced with the readiness of human resources (HR). The hotel industry has a crucial problem of retaining employees where there is a gap between the interests of employees and the interests of the company. The company's inability to determine the causal factors that can cause turnover intention is certainly the beginning of the hotel industry's inability to provide relevant solutions and programs and make employees more loyal. The turnover rate in the hotel industry has increased significantly every year, so that it can harm the company in terms of cost, resources and motivation because the company loses labor. Turnover intention is the main predictor of turnover, so aspects that can affect turnover intention will affect turnover. This study aims to describe and analyze the relationships between variables and dimensions (indicators) in the research model or paradigm developed by the researcher. These variables are polychronicity, job satisfaction, engagement, work environment and turnover intention. This dissertation research uses quantitative methods and is included in the survey research. Testing the conditional process model using path analysis based on OLS (Ordinary Least Square) regression and bootstrap methods using statistical tools SPSS version 23 and PROCESS version 3.4 by Andrew F. Hayes the 92nd model on the research object. The population in this study were employees of the Bandung hotel industry, with a sample of 257 employees. The findings of this study are that the work environment has no effect (p value > 0.05) directly on the variables of job satisfaction, engagement and turnover intention, but is able to interact as a moderator variable so that it effectively moderates the effect of polychronicity on turnover intention through full mediation of job satisfaction and employee engagement (conditional process). This dissertation research produces novelty in the form of society polychronic behavior model through conditional process as a strategy of reducing employee turnover intention.